2018
DOI: 10.1186/s12872-018-0955-5
|View full text |Cite
|
Sign up to set email alerts
|

Serum levels of sclerostin as a potential biomarker in central arterial stiffness among hypertensive patients

Abstract: BackgroundSclerostin is known to be a canonical Wnt/β-catenin signaling pathway inhibitor, while the Wnt/β-catenin signaling pathway is proposed to be involved in the development of arterial stiffness. This study aims to investigate the relationship between serum sclerostin levels and carotid–femoral pulse wave velocity (cfPWV) among hypertensive patients.MethodsFasting blood samples were obtained from 105 hypertensive patients. Patients with cfPWV values of > 10 m/s were classified in the high arterial stiffn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 49 publications
(63 reference statements)
1
10
1
1
Order By: Relevance
“…Whether these higher sclerostin levels are due to increased production by osteocytes or decreased renal or hepatic elimination, is unknown. Of note, as sclerostin is suggested to be involved in arterial stiffness and vascular calcifications [23,24], we critically looked at the plasma sclerostin values of the three South Asian participants with well-controlled hypertension, but these were well within the range of the study population. Interestingly, previous studies showed that circulating sclerostin levels are higher in individuals with prediabetes and diabetes compared with normoglycemic individuals, and that sclerostin levels positively correlate with HbA1c and HOMA-IR [13,[25][26][27][28][29], albeit we could not reproduce this in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Whether these higher sclerostin levels are due to increased production by osteocytes or decreased renal or hepatic elimination, is unknown. Of note, as sclerostin is suggested to be involved in arterial stiffness and vascular calcifications [23,24], we critically looked at the plasma sclerostin values of the three South Asian participants with well-controlled hypertension, but these were well within the range of the study population. Interestingly, previous studies showed that circulating sclerostin levels are higher in individuals with prediabetes and diabetes compared with normoglycemic individuals, and that sclerostin levels positively correlate with HbA1c and HOMA-IR [13,[25][26][27][28][29], albeit we could not reproduce this in our study.…”
Section: Discussionmentioning
confidence: 99%
“…The same authors revealed a negative relationship between augmentation index and sclerostin concentration in 67 healthy adults [15]. However, one should not forget that some authors have shown a positive relationship between the concentration of circulating sclerostin and cIMT and arterial stiffness in adults [12,20,33]. The latter may indicate the complexity of the interaction between the Wnt/beta-catenin system and arterial wall.…”
Section: Discussionmentioning
confidence: 95%
“…The exclusion criteria were: secondary forms of hypertension, the coexistence of known bone pathology, abnormalities in biochemical parameters of calcium-phosphate metabolism, diabetes mellitus, chronic inflammatory disease, or acute infectious disease. Based on available literature on sclerostin, assuming a delta of 4.5 (effect size: 0.50), a 0.05 alpha level, and 80% power, we estimated the sample size at 60 patients [13,14,16,[18][19][20]; 20 age-and sex-matched healthy subjects were included in the control group. In the statistical analysis, the control group was smaller than the study group due to the comparable variance of key parameters in both groups.…”
Section: Study Groupmentioning
confidence: 99%
“…However, the exact relationship of sclerostin and vascular calcification is yet to be established since some publications state a negative [ 51 ], while others no correlation [ 52 ] or a positive correlation between the two [ 53 ]. In the study of Chang et al, which was performed on 105 hypertensive patients, serum sclerostin proved to be an independent predictor of AS in a model containing age, intact parathyroid hormone levels, systolic blood pressure, diabetes, and GFR [ 54 ]. Sclerostin was different in the low and high AS groups, and the cfPWV values were similar to those measured in our study in both groups.…”
Section: Discussionmentioning
confidence: 99%